Molecular cloning and expression of ghrelin in the hypothalamus–pituitary–gastrointestinal tract axis of the Yak (Bos grunniens) in the Qinghai–Tibetan Plateau. (3rd September 2018) - Ding, Yanping; Zhang, Na; Li, Jialong; Jin, Yiran; Shao, Baoping
Abstract: Ghrelin is a very important brain–gut peptide that modulates appetite and energy metabolism in mammals. The yak is the only large mammal that can adapt to the cold temperatures and hypoxia conditions present in the Qinghai–Tibet Plateau. However, there are no reports on ghrelin molecular characterization and expression in the hypothalamus–pituitary–digestive tract axis of the yak to date. In this study, the coding region sequence of the yak ghrelin, containing a complete ORF (351) encoding for 117 amino acids, was cloned. Immunohistochemistry analysis of the yak samples showed that ghrelin‐immunoreactive cells were expressed at the arcuate nucleus (ARC), the ventromedial nucleus (VMN), the dorsomedial nucleus (DMN) of the hypothalamus and also at the anterior pituitary. Ghrelin‐positive cells were also present in approximately two thirds of the submucosa of the abomasum fundic gland and mucous layer of the duodenum intestinal gland. Ghrelin's mRNA highest expression occurred in the abomasum sample, followed by the duodenum, hypothalamus and lowest at the pituitary gland. The level of ghrelin mRNA measured in yak was higher than in cattle for all the tissues that were compared. The ghrelin protein and mRNA expression profiles were similar. These data imply that the high expression of ghrelin in the hypothalamus–pituitary–digestive tract axis of yak could aid adaptation to the extreme environment better than cattle, by improving appetite and fat accumulation, regulating body temperature and reducing energy consumption via regulating energy metabolism.